Charlotte Illes is not a teacher - Siegel, Katie (A Not a Detective mystery, 2024)
Mention “returning to the scene of a crime,” and people don’t usually picture a middle school. But that’s where kid detective Lottie Illes enjoyed some of her greatest successes, solving mysteries and winning acclaim—before the world of adult responsibilities came crashing in . . .Twentysomething Charlotte is now back in the classroom, this time as a substitute teacher. However, as much as she’s tried to escape the shadow of her younger self, others haven’t forgotten about Lottie. In fact, a fellow teacher is hoping for help discovering the culprit behind anonymous threats being sent to her and her aunt, who’s running for reelection to the Board of Education. At first, Charlotte assumes the messages are a harmless prank. But maybe it’s a good thing she left a detective kit hidden in the band room storage closet all those years ago—just in case. Because the threats are escalating, and it’s clear that untangling mysteries isn’t child’s play anymore . . .